Genetic and structural identification of an O-acyltransferase gene (oacC) responsible for the 3/4-O-acetylation on rhamnose III in Shigella flexneri serotype 6 - Knirel, Yuriy A (BioMed Central, 2014)
BACKGROUND: O-antigen (O-polysaccharide) of the lipopolysaccharide is a highly variable cell component of the outer membrane in Shigella flexneri. It defines the serospecificity and plays an important role in the pathogenesis of shigellosis. There are two distinct O-antigen forms for the 19 serotypes of S. flexneri: one for serotypes 1–5, X, Y, 7 (and their subtypes), and the other for serotype 6. Although having different basal O-polysaccharide structures, the two forms share a common disaccharide fragment [→2)-α-l-Rhap(III)-(1 → 2)-α-l-Rhap(II)]. In serotype 6 and some non-6 serotypes, Rha(III) is O-acetylated at position either 3 or 4 (3/4-O-acetylation), conferring to the hosts a novel antigenic determinant named O-factor 9. An acyltransferase gene (oacB) responsible for this modification has been identified in serotypes 1a, 1b, 2a, 5a, and Y, but not in serotype 6. RESULTS: Using genetic, serological, and chemical approaches, another acyltransferase gene named oacC was demonstrated to be responsible for the 3/4-O-acetylation on Rha(III) in the O-antigen of S. flexneri serotype 6. Inactivation of the oacC gene resulted in the loss of the 3/4-O-acetyltion, and the cloned oacC gene restored this modification upon transformation. In accordance with the similarity in the acceptor substrate structure and high sequence homology (72% identity) between oacC and oacB, oacC has the interchangeable function with the oacB gene in mediation of the 3/4-O-acetylation. The oacC gene is located in a prophage on the chromosome and presented in all 77 serotype 6 strains tested. CONCLUSIONS: Identification and functional characterization of the O-acetyltransferase encoding gene, oacC, shows that it is involved in O-antigen modification by 3/4-O-acetylation on Rha(III) specific to serotype 6. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12866-014-0266-7) contains supplementary material, which is available to authorized users.